PENGEMBANGAN SUMBER DAYA MANUSIA APARATUR PADA KANTOR BAPPEDA KOTA PALU - Jariah, Ainun; Hattab, Syahrudin; Daswati, Daswati (Katalogis, 2018)
The study aims to find out the implementation of human resource development at the Office of the Regional Development Planning Board of the Palu City. The main theory in this study was the theory of Human Resource Development by Hasibuan (2011: 72-73) by looking at two aspects namely informal and formal development. The research method use the Qualitative-descriptive. The location in this study was carried out at the Regional Development Planning Agency (BAPPEDA) with as many as 5 informants selected purposively. Data collection is done by conducting interviews, observation, and documentation. Data analysis techniques use the Interactive model of Miles and Huberman. Based on the results of the research on human resource apparatus development at the Bappeda Office of the Palu City in the previous discussion, it can be concluded that from the two aspects namely informal development and overall formal development is adequate, there are still some things that need to be improved in order to improve the quality of resource development can be more maximal.